Analisis Karakteristik Sampah Padat Perkotaan Kategori Kota Kecil dan Kelayakannya Menjadi Bahan Bakar Padat (Studi Pada Wilayah Perkotaan Kalianda, Lampung Selatan): Sampah Padat Perkotaan - Apriyanto, Agus; Yunita Mauliana (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
The municiple solid waste problem currently facing Kalianda City is the lack of appropriate technology that is effective and efficient. This research aims to analyze the characteristics of Kalianda city waste and its feasibility as an alternative energy source by applying appropriate technology. Surveys and investigations of waste generation volume, composition and characteristics have been carried out referring to SNI 19-3964-1994. Characterization of analytical tests such as mouister content, ash content, volatile matter, fixed carbon and chemical elements to calculate the heating value. The measurement results show that the average waste generation in Kalianda City is 0.39 kg/person/day with a composition of 65% organic waste and 35% anorganic waste. Organic waste has a mouister content of 63.05%, ash content of 16.29%, volatile matter of 70.48%, and produces fixed carbon of 44.26%. Empirical calculations after drying the waste until the mouister content was <10%, obtained a calorific value of 4,017.69 kcal/kg to 4,140.62 kcal/kg. The application of torrefaction technology results in an increase in the heating value of up to 5,424.60 kcal/kg to 5,623.29 kcal/kg equivalent to subbituminous coal B which can be used for thermal and electricity generation. The technology is economical, sustainable and uses a relatively small area.